The Influence of Perceived Brand Globalness, Perceived Brand Localness on Healthy Food Products in Indonesia - Rafly Anggiat; Kurniawati Kurniawati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The study sought to investigate the impact of brand globality and brand locality perceptions on brand credibility. Then, examine the impact of brand credibility on your brand relationship. The AMOS program analyzed the hypothesis proposed in this study using a structural equation model (SEM). Purposive sampling with individual units of analysis was employed in this study. Primary data was collected by distributing questionnaires to 200 respondents. According to the findings of this study, perceptions of brand globality and perceptions of brand locality have no positive effect on brand credibility. In contrast, brand credibility has a positive influence on brand relationships with oneself. This research is limited to users of healthy product brands. Future researchers can examine users of healthy product brands in general. This research contributes to providing input to the top management of companies in Indonesia regarding factors that can help achieve and manage consumer loyalty in using healthy food products.